Modelación de emisiones ambientales asociadas a la movilidad. Caso de Estudio: corredor de la calle 13 entre Av. Boyacá y peaje del río Bogotá (2018)
The objective of this project is to generate a model to evaluate the volume of vehicular emissions produced along the corridor. The analysis of results of this model may contribute to stablish public politics for efficient transportation reducing environmental degradation and health issues among the surrounding community. The software used for building the simulation model was PTV Vissim and PTV EnViVer for calculate carbon dioxide (CO₂), nitrogen oxides (NOₓ) and particulate matter (PM₁₀). The corridor of study is located in 13th street in Bogotá also known as Avenida Centenario between Avenida Boyacá and Rio Bogotá Toll. This section of the road is 9 Km long and its one of the main points for the entrance and exit of heavy transportation. The 13th street is also the main access to communicate the dormitory towns of Funza, Madrid, Mosquera and Facatativa, located at the west of Bogotá. Also, the 13th street is the only access one of the largest Dutty Free Zones in Colombia, known as Zona Franca. Over 400 companies operate in Zona Franca, 53% of which are dedicated to logistics, 27% to services, 12% are trading companies and 8% are industrial business. For this study, a methodology was formulated to evaluate the current pollution situation considering twelve elements related to vehicular traffic, such as road infrastructure, conflict areas, coordination of the traffic lights network, mandatory staging points, intermunicipal and public bus stops, vehicular volume, volume composition, definition of vehicular, public transport lines, assignment of vehicular emission factors for each category of vehicles an evaluation node create to obtain operational information about the corridor of study. Also, three scenarios were proposed aimed at reducing contamination along the corridor and to produce an operational enhancement. The results indicate a high rate of pollution product of the heavy traffic along the corridor and also due to the industrial use of the land. Further factors found to be related to emission increase in the 13th street are the heavy traffic long rides used for the Free zone, massive intermunicipal volume of transportation between Bogotá and the dormitory towns and the lack of technical public transportation. At a design level it is important to emphasized the traffic lights effect on the different road intersections in the zone. A number of alternatives of short, medium and long term were proposed to improve emissions within the corridor, which can be replicated by different kind of transport modelation specialists on high traffic volume roads.